Phylogeny and taxonomy of the genus Gliocephalotrichum - L. Lombard (2018)
Species in the genus Gliocephalotrichum (= Leuconectria) (Hypocreales, Nectriaceae) are soilborne fungi, associated with post-harvest fruit spoilage of several important tropical fruit crops. Contemporary taxonomic studies of these fungi have relied on morphology and DNA sequence comparisons of the internal transcribed spacer region of the nuclear rDNA (ITS) and the β-tubulin gene regions. Employing DNA sequence data from four loci (β-tubulin, histone H3, ITS, and translation elongation factor 1-alpha) and morphological comparisons, the taxonomic status of the genus Gliocephalotrichum was re-evaluated. As a result five species are newly described, namely G. humicola (Taiwan, soil), G. mexicanum (rambutan fruit from Mexico), G. nephelii (rambutan fruit from Guatemala), G. queenslandicum (Australia, endophytic isolations) and G. simmonsii (rambutan fruit from Guatemala). Although species of Gliocephalotrichum are generally not regarded as important plant pathogens, their ability to cause postharvest fruit rot could have an impact on fruit export and storage. © 2014 Naturalis Biodiversity Center & Centraalbureau voor Schimmelcultures.